ANALISIS FAKTOR YANG MEMPENGARUHI MAHASISWA MEMILIH FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS MATARAM - Junaidi Sagir; Alamsyah A B; Emilia Septiani (Master of Management, Mataram University, 2021)
The Universities are facing a touggh competition amongst each others to attract the maximum number of eligible candidates. This paper examines the influence facors those are considered by students in making decisions in choosing a higher education for their studies. This research was conducted on new undergraduate students of the 2020 Faculty of Economics and Business, Mataram University, with 100 respondents who were taken proportionally. There are 10 variables studied in this study, namely: reference group, family, social class, campus location, image of study program/faculty, job opportunities, educational facilities, education costs, accreditation status and promotion/communication. The results of the analysis show that from the 10 variables studied previously, they turned into 2 new variables, namely: campus attributes and social interactions which were able to explain up to 70.2% of the total variables studied. Keywords: factor analysis, campus attributes and social interaction